Micro-condensation and identification of separate terpene compounds in an analytical gas chromatograph - Zafra, M. F.; García-Peregrín, E. (Ars Pharmaceutica (Internet), 1970)
A method of collecting small amounts of samples for analysis by infrared spectroscopy, after separation by gas chromatography, using special collectors and cooling with liquid air is described. The cimparativo study of the IR spectra obtained in the direct use of standard substances and those found previous isolation by gas chromatography and microcondensation ("splitting") demonstrates the suitability of the procedure used ...